The role of artisanal mining in the sustainable development of Myanmar's jadeite industry. Issue 126 (December 2021) - Sadan, Mandy; Lawn Dan, Seng
Abstract: Jade is reputed to be the second most valuable gemstone in the world, and its most valuable form, jadeite, is mined in the Kachin State of northern Myanmar. Lauded for its great beauty and cultural significance in neighbouring China, most of the jadeite mined in Myanmar is destined for the Chinese or overseas Chinese markets, where it is made into decorative artefacts. Yet today, the jadeite mines have gained notoriety as sites of environmental and social devastation. The development of large scale mining (LSM) has taken place over the last two decades, largely in the context of attempts to develop political settlements at national and local level to end longstanding conflict. However, the outcomes have exacerbated conflict and seen worsening development outcomes for local people. This paper examines the longer historical tradition of artisanal and small-scale mining (ASM) in the region and considers how, in reassessing the degree to which mining can be brought into the sustainable development agenda, ASM may provide many insights that have previously been overlooked. Highlights: A focus on EITI has inhibited understanding of the importance of ASM in northern Myanmar. We should reconsider how ASM may contribute to local development and the SDGs. Inadequate data inhibits understanding how LSM impacts local communities but the recent census may provide baseline evidence. Discussions about mining and development need to focus on local contexts of mining to limit environmental and social harms.